Analysis of Factors Affecting Consumer Intention in Buying Goods on Social Media (Case Study: XYZ Shop) - Wiandana, I Gede; Suryani, Erma (IPTEK Journal of Proceedings Series, 2020)
The number of internet users worldwide has increased from year to year. Especially in Indonesia, in 2017 internet users have reached 143.26 million people or around 54.68% of the total population in Indonesia and on average use it every day. The growth of internet use in Indonesia was used by business people to run their business by selling where social media is the most used place to sell (64.9%). However, there are still many consumers who are reluctant to make the intention to purchases, this is caused by many factors including the level of consumer confidence, consumer risk perceptions, and others. In this study, the factors that influence consumer behavior will be analyzed about intention purchasing decisions on social media using the developed Theory of Planned Behavior. The case study used is the XYZ store that sells shoes, accessories, and goods on social media. Partial Least Square Method of Structural Equation Modeling (PLS-SEM) is used to analyze the research, where the results of this study are to get the conclusions of significant factors that influence consumer intention to purchases product on social media and recommendations for improvements to XYZ stores to improve sales and get more consumers.